Development Strategy of Service Sector in Conditions of Federal States Entities Autonomy Increasing - Terentyeva, Irina V.; Mukhomorova, Irina V.; Perezhogina, Olga N.; Pugacheva, Natalya B.; Lunev, Alexander N.; Akhmetzyanova, Guliya N.; Lezhnin, Vladimir V.; Gainullina, Rezeda R. (International Review of Management and Marketing, 2016)
The relevance of the study is caused by the necessity to develop the sphere of services as a component of balanced socio-economic development of Federal state’s territories. The purpose of the paper is to define strategies for the development of services in conditions of increasing independence of the Federal State’s entities. A leading approach is the institutional one that considers the strategy of development of service sector in the Federal state as long-term programs of transition to innovative socially oriented type of economic development, reducing interregional differentiation in the level and quality of life of the population, creating equal opportunities for citizens and promoting human development. In the conditions of Federal State entities’ autonomy increasing the strategy of development in the sphere of services consists of citizens’ life conditions and social environment’ quality improving; accelerated development of human potential; competitiveness improving of human and ensuring it economic social sectors’ capital; development of competitive service markets; improving of the efficiency of politico-legal institutions providing social services to the population. Strategies’ defining for the development of services in the conditions of Federal State entities’ autonomy increasing is based on the principles of subsidiarity, sustainability, selectivity, fractals and transvers. Certain strategies of development of services are aimed at reducing territorial socio-economic differentiation to the level, caused by objective differences of the Federation’s entities, as well as ensuring the balance of the revenue base and expenditure commitments. Keywords: Socio-Economic Development, Inter-Territorial Differentiation, Economic Strategy, Management. JEL Classifications: H53, H83, O35